2022
DOI: 10.1093/molbev/msac108
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics and Signatures of Selection in Early Neolithic European Farmers

Abstract: Human expansion in the course of the Neolithic transition in western Eurasia has been one of the major topics in ancient DNA (aDNA) research in the last ten years. Multiple studies have shown that the spread of agriculture and animal husbandry from the Near East across Europe was accompanied by large-scale human expansions. Moreover, changes in subsistence and migration associated with the Neolithic transition have been hypothesized to involve genetic adaptation. Here we present high quality genome-wide data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 150 publications
1
16
0
Order By: Relevance
“…Previous studies also found evidence of natural selection at SLC24A5 in European populations 26,27 and showed that the allele was introduced into Europe in the Neolithic 2,37,38 but our study now further demonstrates that this resulted in a removal of hunter-gatherer ancestry across the wider locus. In a similar but opposite process, the MHC locus has previously been demonstrated to have undergone selection in the ancestry of present-day Europe 239 and specifically in Neolithic Europe 18 . Here, we obtain further robust results for selection at the MHC locus corrected for multiple testing, and demonstrate that this process specifically increased hunter-gatherer ancestry at the locus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also found evidence of natural selection at SLC24A5 in European populations 26,27 and showed that the allele was introduced into Europe in the Neolithic 2,37,38 but our study now further demonstrates that this resulted in a removal of hunter-gatherer ancestry across the wider locus. In a similar but opposite process, the MHC locus has previously been demonstrated to have undergone selection in the ancestry of present-day Europe 239 and specifically in Neolithic Europe 18 . Here, we obtain further robust results for selection at the MHC locus corrected for multiple testing, and demonstrate that this process specifically increased hunter-gatherer ancestry at the locus.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of natural selection in the European Neolithic have either compared allele frequencies or haplotype structure with other ancient and modern populations 2,1821 . However, no study to date has attempted to assign signals of adaptive admixture to a particular ancestry close to the time of admixture.…”
Section: Introductionmentioning
confidence: 99%
“…Some other approaches look at specific time slices in the data but require comparisons with simulations of demographic models that might not always be available for ancient genomes 14 . Other approaches utilize haplotype approaches that are unable to precisely identify the targets of selection 14,15 .…”
Section: Mainmentioning
confidence: 99%
“…According to our results based on a final set of 58 SNPs, the pigmentation patterns highly differ between horizons, as Bk-I mostly possesses variants for light pigmentation, blue eyes and blonde hair, while Bk-II is more similar to populations of Neolithic Europe of darker colouration 23,24 (Fig.1.c), although some variants for lighter pigmentation exist within this group too. Members of Bk-III on the other hand show a wide range from dark to light pigmentation tones and even the presence of variants for red hair (Supplementary Table 5, Supplementary Information section 3.2.1).…”
Section: Resultsmentioning
confidence: 67%
“…Besides monitoring population events, archaeogenetics opens a new window to study health qualities of ancient populations that may lead to a better understanding of the background of recent genetics related diseases. Studies that aimed to uncover variants under selective pressure in Homo sapiens populations, such as Lactase persistence (LCT) or Human Leukocyte Antigen (HLA) genes and pigmentation markers are beginning to thrive [23][24][25][26] . However, variants for rare genetic diseases or aneuploidies are sparsely checked on ancient datasets, except for a few cases, such as the study of the Suontaka grave 27 .…”
Section: Introductionmentioning
confidence: 99%